2017
DOI: 10.1364/ol.42.003638
|View full text |Cite
|
Sign up to set email alerts
|

Truly unentangled photon pairs without spectral filtering

Abstract: We demonstrate that an integrated silicon microring resonator is capable of efficiently producing photon pairs that are completely unentangled; such pairs are a key component of heralded single photon sources. A dual-channel interferometric coupling scheme can be used to independently tune the quality factors associated with the pump and signal and idler modes, yielding a biphoton wavefunction with Schmidt number arbitrarily close to unity. This will permit the generation of heralded single photon states with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 23 publications
2
74
0
Order By: Relevance
“…Using cavity modes with different coupling rates for the idler, pump, and signal has been shown to enable signal-idler states with joint spectral amplitudes that are almost completely separable (implying high purity signal states) [32,33]. The main challenges for creating indistinguishable photons with our proposed architecture is stabilization of the high Q resonance and repeatability of the output filter opening.…”
Section: Discussionmentioning
confidence: 99%
“…Using cavity modes with different coupling rates for the idler, pump, and signal has been shown to enable signal-idler states with joint spectral amplitudes that are almost completely separable (implying high purity signal states) [32,33]. The main challenges for creating indistinguishable photons with our proposed architecture is stabilization of the high Q resonance and repeatability of the output filter opening.…”
Section: Discussionmentioning
confidence: 99%
“…However, the filtering process will cause extra loss. Another solution is the engineering of the joint spectra intensity with microring resonators, such as the recently proposed experimental work and theoretical protocols . A high heralding efficiency is critical for scaling photon numbers due to the exponential increase in losses with number of photons.…”
Section: Photon‐pair Sourcementioning
confidence: 99%
“…An important advantage of our proposed design is its ability to produce photons with very high spectral purity. It has been shown that the spectral purity of photons emitted from a resonator where idler, pump, and signal modes are identical is limited to 92% even for a flat pump spectrum [17,28]. In [17] it was shown that using interferometric coupling to increase the linewidth of the pump relative to the signal and idler enables arbitrarily…”
Section: Spectral Correlations Of Generated Photon Pairsmentioning
confidence: 99%